(untitled) (Ingenieria y Universidad, 2002)
The cut-off magnitude (representative magnitude) Mmín and its variations in space and time are estimatedfor the earthquake catalogue ofColombia. An analysis ofthe methodology and the characteristics of the development of the seismological net of Colombia are presented.